Electromagnetic Fields and Osteoarthritis 2025 - Ray, Marks (Journal of Aging Research And Healthcare, 2025)
This mini review examines the potential efficacy of applying electromagnetic field therapy for purposes of reducing osteoarthritis pain and other related disease features such as frailty, muscle sarcopenia, obesity, bone loss and fragility, and cartilage derangements and degradation in the older adult. Based on selected English language literature published largely on PUBMED between January 2000 and October 2025, papers describing the impact and potential synthetic and disease modifying impact of electromagnetic stimuli are explored. These data reveal a high degree of promise in fostering joint tissue reparative efficacy trends post electromagnetic stimulation. Its usage may allay the extent of the disease and its degree of disablement, while facilitating function.
Keywords: Bone; Cartilage; Electromagnetic Fields; Frailty; Muscle; Osteoarthritis; Obesity Sarcopenia; Pain; Therapy